The influence of degree motivation, quality motivation, career motivation, and economic motivation on the interest of akakom accounting student stephen jambi to attend accounting professional education (PPAk) - Ayu Feranika (LP2M Politeknik Jambi, 2019)
This study aims to determine the Effect of Degree Motivation, Quality Motivation, Career Motivation, and Economic Motivation on the Interests of Accounting Students Akakom Stephen Jambi to Follow Accounting Professional Education (PPAk). The data analysis technique used is using multiple regression. Hypothesis testing uses F statistical test and statistical test t. The results of this study indicate that: (1) Degree Motivation, Quality Motivation, Career Motivation, Economic Motivation simultaneously influence the Accounting Students of Akakom Stephen Jambi to Participate in Accounting Professional Education (PPAk).